New heterobimetallic ferrocenyl derivatives: Evaluation of their potential as prospective agents against trypanosomatid parasites and Mycobacterium tuberculosis - Rivas, Feriannys; Medeiros, Andrea; Rodríguez Arce, Esteban; Comini, Marcelo; Ribeiro, Camila M. [UNESP]; Pavan, Fernando R. [UNESP]; Gambino, Dinorah (Elsevier, 2018)
Searching for prospective agents against infectious diseases, four new ferrocenyl derivatives, [M(L)(dppf)4](PF6), with M = Pd(II) or Pt(II), dppf = 1,1′-bis(dipheny1phosphino) ferrocene and HL = tropolone (HTrop) or hinokitiol (HHino), were synthesized and characterized. Complexes and ligands were evaluated against the bloodstream form of T. brucei, L. infantum amastigotes, M. tuberculosis (MTB) sensitive strain and MTB clinical isolates. Complexes showed a significant increase of the anti-T. brucei activity with respect to the free ligands (>28- and >46-fold for Trop and 6- and 22-fold for Hino coordinated to Pt-dppf and Pd-dppf, respectively), yielding IC50 values < 5 μM. The complexes proved to be more potent than the antitrypanosomal drug Nifurtimox. The new ferrocenyl derivatives were more selective towards the parasite than the free ligands. The Pt compounds were less toxic on J774 murine macrophages (mammalian cell model), than the Pd ones, showing selectivity index values (SI = IC50 murine macrophage/IC50 T. brucei) up to 23. Generation of the {M-dppf} compounds lead to a slightly positive impact on the anti-leishmanial potency. Although the ferrocenyl derivatives were more active on sensitive MTB than the free ligands (MIC90 = 9.88–14.73 μM), they showed low selectivity towards the pathogen. Related to the mechanism of action, the antiparasitic effect cannot be ascribed to an interference of the compounds with the thiol-redox homeostasis of the pathogen. Fluorescence measurements pointed at DNA as a probable target of the new compounds. [Pt(Trop)(dppf)](PF6) and [Pt(Hino)(dppf)](PF6) could be considered prospective anti-T. brucei agents that deserve further research.
Keywords: Ferrocenyl compounds; Leishmaniasis; Mycobacterium tuberculosis; Tropolone derivatives; Trypanosoma brucei